ANALISIS TINGKAT KEPUASAN SISWA DALAM PEMBELAJARAN MATEMATIKA SECARA LURING SELAMA MASA PANDEMI - Yosefina Maria Beto Kelen; Finsensius Yesekiel Naja; Yasinta Yenita Dhiki (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
The purpose of this study was to determine the level of student satisfaction in learning mathematics offline during the pandemic. This research is descriptive qualitative research. The subjects of this study were students of class VIIIB SMPN 2 Wulanggitang, totalling 20 people. Data collection methods used in this study were questionnaires and documentation. Data analysis used descriptive qualitative analysis with percentage technique. The results showed that of the 20 subjects studied, there were 3 students or 15% of the Students whose satisfaction levels in learning mathematics online during the pandemic (P), 16 Students or 80% of students whose satisfaction levels in learning mathematics online during the pandemic period was less satisfied (KP), and one student of 5% student whose satisfaction level in learning mathematics online during the pandemic is not satisfied (TP). This shows that offline learning of mathematics during the pandemic at SMPN 2 Wulanggitang is an obstacle to student satisfaction levels.